English communication in the hospitality industry: the employees' perspective - Hobson, Josephine Mary (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
The purpose of this research project was to explore the English communicative competency of management and supervisory level employees within the South Mrican hospitality industry. The Pro lit English Written Assessment, a competency-based assessment tool, was used to establish a relatively objective measure of the English communicative competency of nineteen managers and supervisors. Thereafter thirteen of these respondents were interviewed to determine their perceptions of their English communicative competency and the impact thereof on their work situation, as well as their perceptions of their learning needs and recommendations for intervention. The researcher selected a multi-method approach to the investigation and sought both quantitative and qualitative data. The assessment revealed that the English reading and writing ability of the respondents is distinctly lower than their recorded education level and inadequate in relation to the tasks they are expected to perform at work. The interviews indicated that the respondents are not aware of their lack of English communicative competency or the implications thereof. However, the respondents expressed important insights into the factors that should be taken into account when planning an educational intervention III an organization. These included the need to incorporate English second language learning principles, to treat the learner as an individual, to involve the learner in the decision-making process, to consider the practical concerns of the learner and to ensure that the programme content is appropriate. Recommendations for human resource practices and research in the hospitality industry are presented.
Keywords: Hospitality industry -- Employees -- Training of -- South Africa; English language -- Study and teaching -- South Africa -- Foreign speakers